2023
DOI: 10.7759/cureus.46683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Dosing on the Efficacy of Tissue Plasminogen Activator and Deoxyribonuclease in the Treatment of Pleural Infection

Vikas Pathak,
Lukash Adhikari,
Christine Zhou

Abstract: Background: The goal of this study was to evaluate how the administration of concurrent tissue plasminogen activator (tPA) and deoxyribonuclease (DNase) therapy with variable dosing for complicated parapneumonic effusions and empyema affects patient outcomes in an inner-city community hospital. Methods: This retrospective analysis was performed at an inner-city hospital located in Raleigh, North Carolina. A list of all patients treated with tPA and DNase between July 1, 2015, and December 31, 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Optimal dosing has not been established yet; however, the currently used regimen is derived from the original MIST 2 trial in which patients received a total of 10 mg of tPA and 5 mg of DNase intrapleurally twice a day in six doses [ 50 ]. However, such dosing might not be optimal in all patients [ 54 ]. An international survey of 49 practicing physicians involved in the management of pleural infections and who were either actively involved in pleural research and publications or were members of relevant pleural disease guideline panels observed a large variation in treatments offered [ 55 ].…”
Section: Managementmentioning
confidence: 99%
“…Optimal dosing has not been established yet; however, the currently used regimen is derived from the original MIST 2 trial in which patients received a total of 10 mg of tPA and 5 mg of DNase intrapleurally twice a day in six doses [ 50 ]. However, such dosing might not be optimal in all patients [ 54 ]. An international survey of 49 practicing physicians involved in the management of pleural infections and who were either actively involved in pleural research and publications or were members of relevant pleural disease guideline panels observed a large variation in treatments offered [ 55 ].…”
Section: Managementmentioning
confidence: 99%